A Swing-Assist Controller for Enhancing Knee Flexion in a Semi-Powered Transfemoral Prosthesis - David M. Marsh; Marco Puliti; Michael Goldfarb (IEEE, 2024)
This work proposes a new swing controller for semi-powered low impedance transfemoral prostheses that resolves the issue of potentially competing inputs between artificial assistive power and user-sourced power. Rather than add power as an exogeneous input, the control approach uses power to modify the homogeneous portion of the shank dynamics, and therefore need not construct or curate an input that is coordinated with user input. The implemented controller requires a single control parameter at a given walking speed, where the value of that parameter is a function of walking speed, as determined by an adaptive algorithm, such that peak knee angles are commensurate with walking-speed-dependent behaviors of individuals without any negative gait pathologies. The controller and parameter selection algorithm are described in the paper, and subsequently validated in walking experiments with three participants with unilateral transfemoral amputation. The experiments demonstrate that the proposed controller increases peak knee angle and minimum toe clearance during swing phase without increasing hip compensatory actions, relative to the users’ daily-use devices.